Training volume and strength and power development - Cronin, J.; Crewther, B. (Journal of Science and Medicine in Sport, 2004)
The purpose of this study was to determine if three training loads equated by volume differed in terms of the temporal, kinematic and kinetic characteristics of each set. Twelve experienced weightlifters (30.2+/-10.6 years old and 75.8+/-13.0 kg) performed three sets (6 x 30% 1RM, 3 x 60% 1RM and 2 x 90% 1RM) of ballistic squats on an instrumented supine squat machine. Repeated measures ANOVA and Tukey HSD post hoc comparisons were used to distinguish significant differences between the three training loads on a variety of temporal, kinematic and kinetic variables. Significantly (p< 0.05) greater total time under tension during the eccentric (41-53%) and concentric phases (27-31%) was observed for the 30% 1RM condition compared to the other two conditions. Similarly, the lighter loading intensity resulted in significantly greater total eccentric (9-19%) and concentric (14-24%) force output compared to the other two conditions. Greater total power output was associated with the 30% 1RM condition for both the eccentric (25-48%) and concentric (40-69%) phases. Greater total work (9-24%) was also associated with the 30% 1RM condition. The 60% 1RM condition produced significantly greater total work, force and power compared to the 90% 1RM condition. However, greater concentric impulse (29-42%) was associated with the 90% 1RM condition. It is suggested that strength and power research needs to adopt a set kinematic and kinetic analysis approach within the research designs so that a better understanding of the nature of the neuromuscular adaptations elicited by different loading parameters is achieved.